f(t) = 11e2t + e6 how do i do this one...? please help
Last edited by mathaction; Oct 2nd 2007 at 09:10 PM.
Follow Math Help Forum on Facebook and Google+
Originally Posted by mathaction f(t) = 11e2t + e6 how do i do this one...? please help If that is f(t) = 11e^(2t) +e^6, then, f'(t) = 11*e^(2t) *2 +0 f'(t) = 22e^(2t) -------------------answer. If that is f(t) = (11e^2)t +e^6, then, f'(t) = (11e^2) +0 f'(t) = 11e^2 ---------------------answer. Reminder, e^2 and e^6 are constants.
View Tag Cloud